Implementation of Corporate Social Responsibility (Compatibility of The Programme with Smes Needs, Smes Capabilities, and Organisations Capabilities) - Nur Chotimah (Universitas Airlangga, 2022)
Corporate Social Responsibility (CSR) emerges as a concept that requires companies not only focus on business profit, or to meet the demands of company shareholders, but also to fulfill the interests of all stakeholders. In Indonesia, implementation of CSR has been regulated by Law Number 40 of 2007 concerning Limited Liability Companies, Article 74, even for State-Owned Enterprises (BUMN). PT. Telkom Jatim as one of BUMN in Indonesia provides CSR to SMEs in Tanggulangin, Sidoarjo. This study aims to describe the compatibility of the CSR programme with SMEs needs, SMEs capabilities, and organisations capabilities of PT. Telkom Jatim for SMEs Tanggulangin, Sidoarjo. This research uses qualitative research methods through in-depth interviews, observation, and documentation. The conclusions obtained from this study are the compatibility of the CSR programme with SME needs, SMEs capabilities, and organisations capabilities to implement CSR of PT. Telkom Jatim in SMEs Tanggulangin, Sidoarjo is appropriate, although there are still things that need to be improved, so that the implementation of the CSR programme PT. Telkom Jatim can meet the expectations of SMEs players and provide positive feedback for the company.